Designing Fan Speed Regulation Software Using Backpropagation Method - Prayogi, Satria Yudha; Sinaga, Sony Bahagia (Devitara Innovations, 2024)
Fans have the main function of air conditioning, room fresheners, and dryers which are usually equipped with heating components. In addition, fans are also used in vacuum cleaners and various decorative elements in the room, which play a role in keeping the air temperature within the specified limits. Advances in the field of computer programming provide many benefits, especially in terms of ease and efficiency in the use of devices connected to computers. With control through a computer, the device can be operated more optimally and responsively according to the needs of the user.